The early results analysis of surgical treatment of supratentorial gliomas with wake-up anesthesia application - Usatov, S. A.; Zalloum, Hatem; Shopin, V. N. (Ukrainian Neurosurgical Journal, 2007)
On the basis of analysis of 66 patients with supratentorial gliomas observation and treatment in the early postoperative period the operation’s efficiency at wake-up anesthesia’s was determined and the reasons for neurological deficiency development were established. Removing of gliomas with dynamic intraoperation testing allowed to avoid neurological symptoms aggravation: in 74% cases of large glioma and in 79% gliomas of average and small size. The neurology deficiency occurrence was usually caused by infiltrative tumor’s growth in functionally significant brain zones, and influence on brain structures during operation. These data has to be taken into consideration while application wake-up and the general anesthesia.